Towards the understanding of the Ti/Al ratio role in solid-state reaction for ohmic contacts on n-GaN. (May 2023) - Guillemin, S.; Messaoudene, S.; Gergaud, P.; Biscarrat, J.; Roulet, P.; Bernier, N.; Templier, R.; Souil, R.; Zucchi, X.; Rodriguez, Ph.
Abstract: The fast-growing market of GaN-based power electronics requires the development of performing ohmic contacts. The Ti/Al stack, being one of the most popular, has been thoughtfully investigated over the years in terms of electrical performances but remains to be better understood in terms of contact formation and related solid-state reactions, especially when targeting small Ti to Al ratios (typically, down to lower than 5 at. %). In this paper, the influence of the deposited Ti layer thickness on the resulting contact is investigated using in-situ and ex-situ XRD methods as well as TEM imaging. It is found that a threshold exists, below which the diffusion phenomena ruling alloy formation during annealing are controlled, leading to a frozen Al3 Ti/Al bi-layer morphology. Past this threshold, the erratic formation of non-textured Al3 Ti grains is observed, which is detrimental to devices performances. The result interpretation is supported by an extended bibliography survey focused on material science, the first of the sort.